Determinación de la calidad del agua por bioindicadores (Macroinvertebrados) en el río Cunuyacu, para una propuesta de manejo de recurso hídrico en el cantón Latacunga, período 2023. - Baltazaca Ante, Monica Alexandra (2023)
The present investigation was carried out with the objective of determining the quality of water in the Cunuyacu River in the city of Latacunga in the province of Cotopaxi, through biological indices (BMWP/col, ABI, E.P.T, Shannon – Weaver) and physical analysis. chemical, in order to establish the water resource management proposal, for this the qualitative method was considered to delimit the sampling points along the route of the river (P 1 Locoa, P2 Colegio Trajano Naranjo, P3 Molinos Poultier) and the In the same way, it was examined to classify the individuals according to the taxonomic classification of class, order and family, the quantitative method was used to count the macroinvertebrates that were collected at three sampling points, the inductive method was considered to determine the level of contamination of the river. The results obtained through the BMWP/col index at three sampling points present a critical water quality, ABI and E.P.T both indices indicate poor water quality, with respect to the Shannon - Weaver index at the three points it presents a low diversity, 1557 individuals of aquatic macroinvertebrates were identified distributed in 18 families, in the first point 78 individuals were obtained, while in point 2 a greater number of individuals was obtained with a total of 1079, in the last point 400 individuals were found, the Index of Water Quality presents a poor water quality, in which the following physical and chemical parameters were analyzed: COD, pH, nitrate, chromium, calcium, magnesium, temperature, conductivity and dissolved oxygen. With the results obtained from the biological indices and Water Quality Index, through the problem tree the causes and effects present in the Cunuyacu River were identified for which proposals for water resource management strategies were proposed. The Cunuyacu River has poor water quality due to different anthropogenic activities carried out by humans, which is why it is necessary to make the current state of the river known to local residents through socialization and education campaigns. environmental in this way take measures to reduce the negative effects of the water resource.